Relasi Akal dan Wahyu Era Modern (Analisis Teologis Pemikiran Ibnu Taymiyyah) - Sindi Lestari; Ismail Ismail (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: The results of this study are; 1) Ibn Taymiyyah adheres to tauhid uluhiyah because rububiyyah has included it. Ibn Taimiyah divided the concept of Tauhid into three parts, Tauhid Asma' Wa-asshifat, Tauhid Uluhiyyah and Tauhid Rububiyah. Ibn Taimiyyah prioritized revelation over reason, revelation was considered higher than reason but did not leave reason behind, he equated reason and revelation by viewing the position of reason as